Anti-pollution type aluminum-based lithium adsorbent and preparation method thereof

CN118767890BActive Publication Date: 2026-11-03BEIJING TAIFENG XIANXING NEW ENERGY TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410943932.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-15
Publication Date
2026-11-03
Estimated Expiration
2044-07-15

AI Technical Summary

Technical Problem

Existing commercial aluminum-based lithium adsorbents exhibit poor anti-fouling ability in potassium and boron extraction tailings, leading to a decline in adsorption capacity, especially in brine containing organic flotation reagents and complexing agents, where mass transfer efficiency decreases.

Method used

In the preparation of aluminum-based lithium adsorbents, hydrophilic polymer materials polyacrylonitrile and polyvinyl alcohol membranes are introduced to enhance the interfacial polarity and smoothness of the adsorbent, reduce the adsorption of organic pollutants, and improve the anti-pollution ability.

Benefits of technology

The prepared anti-fouling aluminum-based lithium adsorbent maintains stable adsorption capacity and selectivity in lithium-containing brine, avoiding a significant decline in adsorption capacity with increasing number of runs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118767890B_ABST
    Figure CN118767890B_ABST
Patent Text Reader

Abstract

The application discloses an anti-pollution type aluminum-based lithium adsorbent and a preparation method thereof, and belongs to the technical field of salt lake lithium extraction adsorption. The anti-pollution type aluminum-based lithium adsorbent is prepared by the following steps: preparing aluminum-based adsorbent powder and preparing a molding base fluid, obtaining an adsorbent molding agent by mixing the aluminum-based adsorbent powder and the molding base fluid, obtaining an adsorbent precursor particle by molding the adsorbent molding agent, and finally obtaining the anti-pollution type aluminum-based lithium adsorbent by a post-treatment process of the adsorbent precursor. The anti-pollution type aluminum-based lithium adsorbent prepared by the application has better anti-pollution capability in lithium-containing brine produced after potassium and boron extraction tail liquid, and does not significantly degrade with the increase of the operation frequency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of lithium extraction adsorption technology in salt lakes, specifically relating to an anti-pollution aluminum-based lithium adsorbent and its preparation method. Background Technology

[0002] The technological difficulty and cost of lithium extraction from salt lake brine are mainly affected by the lithium concentration and magnesium-to-lithium ratio in the brine. Because lithium and magnesium have very similar properties and hydration radii, the higher the magnesium-to-lithium ratio in the brine, the greater the difficulty of lithium extraction. In Qinghai, my country, salt lake brine possesses the characteristics of a high magnesium-to-lithium ratio and low lithium-ion concentration. Therefore, in the past few decades, lithium extraction technology from raw brine in Qinghai salt lakes has been relatively immature. Traditional lithium extraction routes are established at the downstream end of potash and boron fertilizer production lines, with lithium mainly existing as a byproduct of potash and boron production, resulting in low overall extraction efficiency. In recent years, after breakthroughs in high magnesium-to-lithium ratio brine lithium extraction technology, represented by the "adsorption method," the lithium extraction capacity of Qinghai salt lakes has grown rapidly. The adsorption method has mature applications in water treatment, pharmaceuticals, food, and hydrometallurgy, but lithium extraction from salt lakes is still a blue ocean market. The adsorption method has become one of the most widely used and promising processes for lithium extraction from salt lakes, with a rapid increase in industrialization projects in the Qinghai region. The core of this technology lies in the selective adsorption material for lithium ions. Currently, the mainstream commercial lithium adsorbent material is an aluminum-based layered hydroxide (Li-Al-LDHs). Aluminum-based lithium adsorbents have advantages such as simple preparation, fast adsorption rate, high selectivity, recyclability, and almost no solubility in neutral pH environments, making them suitable for most salt lake brines in Qinghai Province. However, mainstream commercial aluminum-based lithium adsorbents generally suffer from poor anti-fouling ability, especially in lithium-containing brine generated after potassium and boron extraction tailings. After long-term operation, the adsorbent's adsorption capacity significantly declines. The fundamental reason is the presence of large amounts of organic flotation reagents (such as octadecylamine, dodecylmorpholine, sodium dodecyl sulfonate, etc.) and complexing agents (such as EDTA, diethanolamine, polyacrylic acid, etc.) in the potassium and boron extraction tailings. These organic substances cause severe fouling at the lithium adsorbent interface, leading to pore blockage and a significant decrease in mass transfer efficiency, macroscopically manifested as a decline in the adsorbent's lithium adsorption capacity. Summary of the Invention

[0003] The purpose of this invention is to provide an anti-pollution aluminum-based lithium adsorbent and its preparation method, thereby improving the anti-pollution ability of the aluminum-based lithium adsorbent in the lithium-containing brine generated after potassium and boron extraction tailings.

[0004] The technical solution adopted by the present invention to achieve the above objectives is as follows:

[0005] A method for preparing an anti-pollution aluminum-based lithium adsorbent includes the following steps:

[0006] 1) Preparation of aluminum-based adsorbent powder: Lithium source and aluminum source are mixed and completely dissolved. After adding alkaline solution, a precipitate is formed. The pH of the reaction is controlled to be weakly acidic. Then, a constant temperature water bath reaction is carried out. After the reaction is completed, the mixture is aged, filtered and dried to obtain aluminum-based adsorbent powder.

[0007] 2) Preparation of adsorbent forming agent: Dissolve the organic binder fully in an organic solvent to obtain the forming base liquid, and mix the aluminum-based adsorbent powder and the forming base liquid to obtain the adsorbent forming agent;

[0008] 3) Adsorbent forming: The adsorbent forming agent is evenly dropped into water using a pelletizing device to obtain adsorbent precursor particles;

[0009] 4) Post-treatment of adsorbent precursor: The adsorbent precursor particles are soaked in a polyvinyl alcohol aqueous solution for a period of time, then filtered and dried to obtain an anti-pollution aluminum-based lithium adsorbent.

[0010] Furthermore, in step 1), the mass ratio of lithium source to aluminum source is (0.5 to 1):1.

[0011] Furthermore, in step 1), the pH of the reaction is controlled to be between 4.0 and 6.0.

[0012] Furthermore, the constant temperature water bath reaction conditions in step 1) are: 40–90℃, reaction time 2–5 h.

[0013] Furthermore, the aging time in step 1) is 4–24 hours.

[0014] Further, in step 2), the mass ratio of organic binder to organic solvent is (0.5 to 1):1.

[0015] Furthermore, in step 2), the organic binder is selected from one or more of the following: polyurethane, polyvinyl chloride, polyamide, polyethersulfone, polysulfone, polyacrylonitrile, polyvinylidene fluoride, and polytetrafluoroethylene.

[0016] Furthermore, in step 2), the organic solvent is selected from one or more of ethyl acetate, N,N-dimethylacetamide, and N-methylpyrrolidone.

[0017] Further, in step 2), the mass ratio of aluminum-based adsorbent powder to molding base liquid is (0.62~0.95):1.

[0018] Furthermore, in step 4), the mass concentration of the polyvinyl alcohol aqueous solution is 0.1-2%, and the molecular weight of the polyvinyl alcohol is 25,000-35,000 or 120,000-300,000.

[0019] Further, in step 4), the adsorbent precursor particles are soaked in a polyvinyl alcohol aqueous solution for 2–3 hours.

[0020] Furthermore, the drying conditions in step 4) are: drying at 60–100°C for 1–2 hours.

[0021] An anti-pollution aluminum-based lithium adsorbent is prepared by the above-described preparation method.

[0022] The beneficial effects achieved by this invention are as follows:

[0023] Traditional adsorbent molding substrates are generally hydrophobic polymers with weak interfacial polarity. Organic pollutants are more easily adsorbed at the interface of these weakly polar materials. This leads to severe adsorption capacity decay during circulation in the lithium-containing brine generated after potassium and boron extraction tailings. In contrast, this invention, when preparing an anti-fouling aluminum-based lithium adsorbent, incorporates a hydrophilic organic polymer, polyacrylonitrile (PAC), during the adsorbent molding process. PAC is a polymer made from acrylonitrile monomers, possessing a linear chain structure with repeating units of -CH2-CH(CN)-. Because the carbon-carbon bonds on the polymer backbone are single bonds, the chain is flexible and can move to a certain extent, facilitating the material's ability to be processed into fibers or membranes. Equally important is the presence of the nitrile (-CN) group, which is polar, meaning it attracts water molecules, giving PAC a certain degree of hydrophilicity or water absorption. The addition of PAC increases the interfacial polarity of the resulting adsorbent material, weakening the binding ability of organic pollutants in the water to the adsorbent interface, making these organic pollutants more easily washed away by water flow. On the other hand, during the post-treatment of the adsorbent precursor, a smooth polyvinyl alcohol film is introduced at the adsorbent interface, reducing the roughness of the adsorbent interface and making it difficult for pollutants in the brine to accumulate at the adsorbent interface. This results in the prepared adsorbent exhibiting very strong anti-fouling properties on a macroscopic scale. The anti-fouling aluminum-based lithium adsorbent prepared in this invention maintains stable lithium adsorption capacity, lithium selectivity, and lithium extraction efficiency when circulated in the lithium-containing brine generated after potassium and boron extraction tailings, without significant degradation with increasing number of runs. Attached Figure Description

[0024] Figure 1 This is a picture of an anti-pollution aluminum-based lithium adsorbent.

[0025] Figure 2 This is a scanning electron microscope (SEM) image of the interface of an anti-pollution aluminum-based lithium adsorbent.

[0026] Figure 3 This is a comparison diagram of the interfacial hydrophilicity of the anti-pollution aluminum-based lithium adsorbent before and after the addition of polyacrylonitrile.

[0027] Figure 4 These are long-term test curves of two sets of aluminum-based adsorbents in the adsorption and lithium extraction of lithium from the lithium-containing brine in the potassium-boron extraction tail liquid. Detailed Implementation

[0028] To make the various technical features, advantages, or effects of the present invention more apparent and understandable, a detailed description is provided below in conjunction with the accompanying drawings.

[0029] Example 1:

[0030] This embodiment specifically discloses a method for preparing an anti-pollution aluminum-based lithium adsorbent, including the following steps:

[0031] 1. Preparation of aluminum-based adsorbent powder: A lithium source (containing lithium raw materials, such as lithium carbonate and lithium hydroxide) and an aluminum source (containing aluminum raw materials, such as alumina and boehmite) are mixed in a mass ratio of 0.7:1 and completely dissolved. After adding alkaline solution, a precipitate is formed. The final reaction pH is controlled to 5.5, and then the reaction is carried out in a constant temperature water bath at 60°C for 4 hours. After the reaction is complete, the mixture is aged for 4 hours, filtered, and the resulting powder is dried to obtain aluminum-based adsorbent powder.

[0032] 2. Preparation of adsorbent forming agent: Dissolve the organic binder polyurethane in the organic solvent ethyl acetate at a mass ratio of 0.6:1 to obtain the forming base liquid; mix the aluminum-based adsorbent powder and the forming base liquid at a mass ratio of 0.73:1 to obtain the adsorbent forming agent.

[0033] 3. Adsorbent Forming: The adsorbent forming agent is evenly dropped into water using a pelletizing device to obtain adsorbent precursor particles with a particle size of approximately 1 mm.

[0034] 4. Post-treatment of adsorbent precursor: The adsorbent precursor particles were soaked in a 0.5% (molecular weight 220,000 to 300,000) aqueous solution for 2 hours, filtered, and dried at 80°C for 2 hours to obtain an anti-pollution aluminum-based lithium adsorbent.

[0035] Figure 1 This is a physical image of the anti-pollution aluminum-based lithium adsorbent prepared in this embodiment. Figure 2 This is a scanning electron microscope (SEM) image of the interface of the anti-pollution aluminum-based lithium adsorbent prepared in this embodiment.

[0036] Example 2:

[0037] This embodiment specifically discloses a method for preparing an anti-pollution aluminum-based lithium adsorbent, including the following steps:

[0038] 1. Preparation of aluminum-based adsorbent powder: Lithium source and aluminum source were mixed and completely dissolved in a mass ratio of 0.5:1. After adding alkaline solution, a precipitate was formed. The final reaction pH was controlled to 4.0, and then the reaction was carried out in a constant temperature water bath at 90℃ for 2 hours. After the reaction was completed, the mixture was aged for 12 hours, filtered, and the resulting powder was dried to obtain aluminum-based adsorbent powder.

[0039] 2. Preparation of adsorbent forming agent: Dissolve the organic binder polyvinyl chloride in the organic solvent N,N-dimethylacetamide at a ratio of 0.5:1 to obtain the forming base liquid; mix the aluminum-based adsorbent powder and the forming base liquid at a mass ratio of 0.62:1 to obtain the adsorbent forming agent.

[0040] 3. Adsorbent Forming: The adsorbent forming agent is evenly dropped into water using a pelletizing device to obtain adsorbent precursor particles with a particle size of approximately 0.5 mm.

[0041] 4. Post-treatment of adsorbent precursor: The adsorbent precursor particles were soaked in a 0.1% (w / w) aqueous solution of polyvinyl alcohol (molecular weight 120,000 to 150,000) for 3 hours, filtered, and dried at 60°C for 2 hours to obtain an anti-pollution aluminum-based lithium adsorbent.

[0042] Example 3

[0043] This embodiment specifically discloses a method for preparing an anti-pollution aluminum-based lithium adsorbent, including the following steps:

[0044] 1. Preparation of aluminum-based adsorbent powder: Lithium source and aluminum source were mixed in a 1:1 mass ratio and completely dissolved. After adding alkaline solution, a precipitate was formed. The final reaction pH was controlled to 6.0, and then the reaction was carried out in a constant temperature water bath at 40℃ for 5 hours. After the reaction was completed, the mixture was aged for 24 hours, filtered, and the resulting powder was dried to obtain aluminum-based adsorbent powder.

[0045] 2. Preparation of adsorbent forming agent: Dissolve the organic binder polyamide in the organic solvent N-methylpyrrolidone at a ratio of 1:1 to obtain the forming base liquid; mix the aluminum-based adsorbent powder and the forming base liquid at a mass ratio of 0.95:1 to obtain the adsorbent forming agent.

[0046] 3. Adsorbent Forming: The adsorbent forming agent is evenly dropped into water using a pelletizing device to obtain adsorbent precursor particles with a particle size of approximately 0.8 mm.

[0047] 4. Post-treatment of adsorbent precursor: The adsorbent precursor particles were soaked in a 2% (w / w) aqueous solution of polyvinyl alcohol (molecular weight 25,000 to 35,000) for 2 hours, filtered, and dried at 100°C for 1 hour to obtain an anti-pollution aluminum-based lithium adsorbent.

[0048] Product Test 1 – Hydrophilicity Test:

[0049] The performance of the antifouling aluminum-based lithium adsorbent prepared in Example 1 was tested, and the hydrophilicity before and after the addition of polyacrylonitrile was compared. Figure 3 As shown. By Figure 3The results show that when no polyacrylonitrile was added to the adsorbent substrate, the water contact angle at the adsorbent interface was 24.7°. When polyacrylonitrile was added to the adsorbent, the water contact angle at the adsorbent interface decreased to 21.0°. This demonstrates that the water contact angle significantly decreased after the introduction of polyacrylonitrile into the adsorbent, which fully proves that the hydrophilicity of the prepared adsorbent interface was significantly improved, indicating that the adsorption efficiency was significantly improved within the same time frame after the addition of polyacrylonitrile to the adsorbent substrate.

[0050] Product Test 2 – Control Test:

[0051] Taking the lithium-containing brine generated after potassium and boron extraction tailings from Qinghai Lithium Resources Company as an example, the brine composition is shown in Table 1 below.

[0052] Table 1. Composition of brine in potassium and boron extraction tailings

[0053]

[0054] The anti-fouling aluminum-based lithium adsorbent prepared in Example 1 and a traditional aluminum-based adsorbent were subjected to long-term adsorption and lithium extraction operation on the above-mentioned brine, and the change in lithium adsorption capacity was monitored. The test results are shown below. Figure 4 The results showed that during the 30 testing cycles, the lithium adsorption capacity of the traditional aluminum-based adsorbent decreased from 1.8 g / L to 1.3 g / L, while the capacity of the anti-fouling aluminum-based lithium adsorbent remained at around 1.8 g / L throughout the testing cycle. This experiment strongly confirms the stability of lithium adsorption and extraction by the anti-fouling aluminum-based lithium adsorbent during long-term operation.

[0055] The anti-pollution aluminum-based lithium adsorbents prepared in Examples 2-3 showed similar technical effects after the above two tests.

[0056] Although the present invention has been disclosed above with reference to embodiments, it is not intended to limit the present invention. Appropriate modifications or equivalent substitutions made by those skilled in the art to the technical solutions of the present invention should be covered within the protection scope of the present invention, which is defined by the claims.

Claims

1. A method for preparing an anti-pollution aluminum-based lithium adsorbent, comprising the following steps: 1) After the lithium source and aluminum source are mixed and completely dissolved, an alkaline solution is added to form a precipitate. The pH of the reaction is controlled to be weakly acidic, and then a constant temperature water bath reaction is carried out. After the reaction is completed, the mixture is aged, filtered and dried to obtain aluminum-based adsorbent powder. 2) The organic binder is fully dissolved in an organic solvent to obtain a molding base liquid, and the aluminum-based adsorbent powder and the molding base liquid are mixed to obtain an adsorbent molding agent; the organic binder is selected from one or more of polyurethane, polyvinyl chloride, polyamide, polyethersulfone, polysulfone, polyacrylonitrile, polyvinylidene fluoride, and polytetrafluoroethylene. 3) Use a pelletizing device to evenly drop the adsorbent forming agent into water to obtain adsorbent precursor particles; 4) The adsorbent precursor particles were soaked in a polyvinyl alcohol aqueous solution for a period of time, then filtered and dried to obtain an anti-pollution aluminum-based lithium adsorbent.

2. The preparation method according to claim 1, characterized in that, In step 1), the mass ratio of lithium source to aluminum source is (0.5~1):

1.

3. The preparation method according to claim 1, characterized in that, In step 1), control the pH of the reaction to 4.0~6.0; constant temperature water bath reaction conditions: 40~90℃, reaction time: 2~5h; aging time: 4~24h.

4. The preparation method according to claim 1, characterized in that, In step 2), the mass ratio of organic binder to organic solvent is (0.5~1):

1.

5. The preparation method according to claim 4, characterized in that, In step 2), the organic solvent may be one or more of ethyl acetate, N,N-dimethylacetamide, and N-methylpyrrolidone.

6. The preparation method according to claim 1, characterized in that, In step 2), the mass ratio of aluminum-based adsorbent powder to molding base liquid is (0.62~0.95):

1.

7. The preparation method according to claim 1, characterized in that, In step 4), the mass concentration of the polyvinyl alcohol aqueous solution is 0.1-2%, and the molecular weight of polyvinyl alcohol is 25,000-35,000 or 120,000-300,000.

8. The preparation method according to claim 1, characterized in that, In step 4), the adsorbent precursor particles are soaked in a polyvinyl alcohol aqueous solution for 2-3 hours.

9. The preparation method according to claim 1, characterized in that, The drying conditions in step 4) are: drying at 60~100℃ for 1~2 hours.

10. A pollution-resistant aluminum-based lithium adsorbent, characterized in that, It is prepared by the preparation method according to any one of claims 1-9.

Citation Information

Patent Citations

  • Mesoporous aluminum-based lithium adsorbent as well as preparation method and application thereof

    CN116272843A

  • Lithium adsorbent and preparation method and application thereof

    CN116440869A